Changes in visual attention towards food cues after obesity surgery: An eye-tracking study. (October 2020) - Schäfer, Lisa; Schmidt, Ricarda; Müller, Silke M.; Dietrich, Arne; Hilbert, Anja
Abstract: Research documented the effectiveness of obesity surgery (OS) for long-term weight loss and improvements in medical and psychosocial sequelae, and general cognitive functioning. However, there is only preliminary evidence for changes in attentional processing of food cues after OS. This study longitudinally investigated visual attention towards food cues from pre- to 1-year post-surgery. Using eye tracking (ET) and a Visual Search Task (VST), attentional processing of food versus non-food cues was assessed in n = 32 patients with OS and n = 31 matched controls without weight-loss treatment at baseline and 1-year follow-up. Associations with experimentally assessed impulsivity and eating disorder psychopathology and the predictive value of changes in visual attention towards food cues for weight loss and eating behaviors were determined. During ET, both groups showed significant gaze duration biases to non-food cues without differences and changes over time. No attentional biases over group and time were found by the VST. Correlations between attentional data and clinical variables were sparse and not robust over time. Changes in visual attention did not predict weight loss and eating disorder psychopathology after OS. The present study provides support for a top-down regulation of visual attention to non-food cues in individuals with severe obesity. No changes in attentional processing of food cues were detected 1-year post-surgery. Further studies are needed with comparable methodology and longer follow-ups to clarify the role of biased visual attention towards food cues for long-term weight outcomes and eating behaviors after OS.